The Effect of Denture Cleanser Materials on Impact Strength of Heat Cure Acrylic Resin (Mustansiria Dental Journal, 2018)
Acrylic denture base is the part of the denture that rests on the foundation tissue &to which the teeth are attached. The main objective of this study was to determine theeffect of different cleansers solution on the impact strength of heat cure acrylic resin.Thirty (30) rectangular shape samples from acrylic were prepared with dimension of(55 mm *10 mm *2.5 mm) length, width& thickness .The acrylic was fabricated inthe same conventional way for construction base palate. All the specimens wereexamined by vernier before immersion in solution to check the size of each samples,the samples were divided into three group (A, B& C) each group contain ten samples.The samples in first group (A) were immersed in distilled water, the samples insecond group (B) were immersed in peroxide solution, while the sample in the thirdgroup (C) were immersed in prepared cleanser solution (citric acid).After period ofimmersion (for 3 week & 15 minutes every day).Finally each samples rinsed bydistilled water & cleaned thoroughly by apiece of cotton before testing. The impactstrength was tested in chapy impact machine. The statistical analysis of the resultsshowed that there was no statically significant difference in impact strength valueamong the testing groups. This means that the all cleanser solution that were used inthis study had no effect on the impact strength